THE ROLE OF THE WORK PLACEMENT OF EMPLOYEES TO THE IMPROVEMENT OF THEIR WORK PRODUCTIVITY AT LIMITED LIABILITY COMPANY OF PT. HARDO SOLOPLAST - Enggar, Neny; Santosa TH, Djoko; Widodo, Jumiyanto (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2013)
The objectives of this research are to investigate and describe: (1) the implementation of work placement conducted at the limited liability company of PT. Hardo Soloplast Karanganyar; (2) the factors which support the implementation of the work placement at the limited liability company of PT. Hardo Soloplast Karanganyar; (3) the factors which hamper the implementation of the work placement at the limited liability company of PT. Hardo Soloplast Karanganyar; and the efforts taken to deal with the constraints in the implementation of the work placement at the limited liability company of PT. Hardo Soloplast Karanganyar.This research used the descriptive embedded single case study with the qualitative approach. The sources of the data of the research were informants, places and events, documents, and archives. The samples of the research were taken by using the purposive-snowball sampling technique. The data of the research were gathered through in-depth interview, observation, and documentation. They were validated by using the data source and data gathering method triangulations, and were then analyzed by using the interactive technique of analysis comprising data reduction, data display, conclusion drawing.The results of the research are as follows: 1) The implementation of work placement conducted at at the limited liability company of PT. Hardo Soloplast Karanganyar has been fairly good. The work placement is done to the new and old employees. The former are exposed to orientation and training, whereas the old ones are exposed to promotion, mutation, and demotion. Such a work placement can improve the work productivity of the new and old employees. 2) The factors which support the implementation of the work placement at the limited liability company of PT. Hardo Soloplast Karanganyar include: (a) education, (b) work experiencce, and (c) health od the employees. With a good health, the work will run smoothly, and their work productivity will also increase. 3) The factors which inhibit the implementation of the work placement are the incompability among the employees, and the high rotation of the employees. 4) The efforts taken to deal with such constraints are conducting monthly togetherness program and improving the prosperity of the employees respectively.